The competitiveness of direct service versus transshipment service : an empiricl analysis of the West Africa-Northern Europe maritime route - (:unkn) unknown (My University, 2017)
This paper raises the question of competitiveness in the regular maritime service by comparing direct service with transshipment. The costing model used for this purpose is applied to the West African-Northern European maritime route with Tangier Med as a transshipment port. The results of the estimates and comparisons indicate, on the whole, that the transshipment is economically advantageous to the ship-owner as a direct service.
Keywords: African Research